Assessment Methods. (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Alternative assessment is type of assessment practice that seeks to assess learners’ language abilities, in ways other than how traditional standardized tests did. The present article reviews the issues related to alternative assessment and adopts a partly critical position regarding some of the related arguments. The advantages as well as quality concerns are discussed and a number of challenges that need to be dealt with are considered. Finally suggestions are made to ameliorate practice.